La Contemporary oligarchy: the government of few disguised as democracy (2018)
It has been sold us the idea of democracy as the government of the people, where the social interests are represented by a single person elected by the society itself. The present proyect pretends, among many others objectives, put into question this definition througth a deductive analysis of the polls made by our investigation group along the last months. In Colombia the act of not voting has become a general action since the half of the last century until today, and although democracy is not just voting, this exercise is a general feature in democratic societies and a categorical factor in knowing the will of the majority. Our final purpose is that to the end of this work the reader may question if the abstentionism phenomenon corresponds to a lack of credibility in democracy, to the desinterest and desinformation of the people, or both.